Establishment and verification of prediction models of creep instability points of asphalt mixtures at high temperatures. (20th May 2018) - Gu, Xingyu; Zhang, Xiaoyuan; Lv, Junxiu
Highlights: Prediction model of the creep instability points of mixtures was established. The instability points of the same gradation mixtures can be predicted. Method for establishing models can study high-temperature performances of mixtures. Abstract: This study established and verified prediction models of the creep instability points of two densely graded asphalt mixtures at high temperatures. First, AC-13 and AC-20 asphalt mixtures were selected and prepared. Their compressive strength values under different confining pressures and shear strength parameters were obtained through triaxial compression tests at 60 °C. Second, multiple repeated pressure values, which were less than the compressive strength values under the same confining pressure, were applied in dynamic triaxial creep tests at 60 °C, and the rheological numbers ( FN ) corresponding to the creep instability points of the asphalt mixtures were obtained. Third, prediction models of the different asphalt mixtures were established by analyzing the change law of FN under different confining and cyclic loading pressures. Finally, the FN values of the different additive mixtures were forecasted using the models. The reliability of the prediction results was successfully verified by the test results. The predicted FN values of the two asphalt mixtures were consistent with the experimental results at 60 °C. The proposed prediction models and the model establishment method can be of great significance in investigating the properties of asphalt mixtures at high temperatures and asphalt pavement rutting.